Shorty the Puppy: Good Puppy! - Webster, James (Ginn and Company Ltd, 1981)
This book lead on to rescue Stories, More rescue stories and rescue adventures.
Keywords: Juvenile literature-English Language readers-Primary-Fiction-Childrens-Africa (English)